2015
DOI: 10.5614/j.eng.technol.sci.2015.47.3.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surfactant Characteristics on IFT to Improve Oil Recovery in Tempino Light Oil Field Indonesia

Abstract: Abstract. Water injection has been employed in the Tempino oil field since 1996. The current oil recovery factor is 35% of OOIP. Even though the pressure is still high, the oil production rate has declined rapidly and the water cut is approaching 89%. In order to mobilize the oil from the reservoir more effectively, surfactant flooding is one of the solutions that can reduce residual oil saturation. Interaction between crude oil and compatible surfactant generates microemulsion, as an indication of low interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The surfactants were pre-screened from dozens of surfactant samples. The surfactant screening method followed Swadesi, et al [20]. …”
Section: Methodsmentioning
confidence: 99%
“…The surfactants were pre-screened from dozens of surfactant samples. The surfactant screening method followed Swadesi, et al [20]. …”
Section: Methodsmentioning
confidence: 99%
“…IFT result on the previous research shows that the utilization of sugarcane bagasse SLS surfactant with similar concentration and salinity levels was able to generate stable IFT value of 4.501 mN/m for Fir wood SLS surfactant and stable IFT value of 6.6995 mN/m for sugarcane bagasse surfactant. IFT test results has proven that sugarcane bagasse NaLS surfactant and Fir wood surfactant was able to lower IFT value on sampled oil and formation water (without surfactant) with IFT value of 12.43 (mN/m) with formation water salinity of 8,110 ppm (Swadesi et al, 2015). Fir wood surfactant is able to lower IFT as much as 7.929 mN/m or 63.78% of the initial IFT value, meanwhile sugarcane bagasse surfactant is able to lower IFT as much as 5.6305 mN/m or 46.10% of the initial IFT value (Chattopadhyay & Webster, 2009;Kosmulski et al, 2004;.…”
Section: Resultsmentioning
confidence: 99%
“…The type of oil used in this research is intermediate crude oil. Interfacial tension test between crude oil and brine samples shows that IFT on oil with formation water (without surfactant) is at IFT = 12.43 (mN/m) with formation water salinity on the sample point at 8,110 ppm (Swadesi et al, 2015). Thermal stability test is conducted to acknowledge surfactant endurance against certain temperature level.…”
Section: Methodsmentioning
confidence: 99%
“…There is a correlation between chemical structure of surfactant and its physical properties (Fujimoto 1985). Swadesi et al (2015) conducted laboratory tests of various surfactants for Tempino field, and showed that surfactant with HLB between 11 and 12 has low interfacial tension of oil-brine, which was performed at total brine salinity 15,540 ppm. However, different oil and brine compositions should have a different optimum range HLB value.…”
Section: Resultsmentioning
confidence: 99%